2009
DOI: 10.1029/2009jg001074
|View full text |Cite
|
Sign up to set email alerts
|

Gross primary production variability associated with meteorology, physiology, leaf area, and water supply in contrasting woodland and grassland semiarid riparian ecosystems

Abstract: [1] Understanding ecosystem-atmosphere carbon exchanges in dryland environments has been more challenging than in mesic environments, likely due to more pronounced nonlinear responses of ecosystem processes to environmental variation. To better understand diurnal to interannual variation in gross primary productivity (GPP) variability, we coupled continuous eddy-covariance derived whole ecosystem gas exchange measurements with an ecophysiologic model based on fundamental principles of diffusion, mass balance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 99 publications
(152 reference statements)
4
19
0
1
Order By: Relevance
“…In GRA, correlations between anomalies in mean EVI (and NDVI) and anomalies in GPP suggest that interannual variability in GPP in grasslands is tightly coupled to leaf area and supports the hypothesis that grasslands use LAI regulation to avoid moisture stress (Jenerette et al, 2009). Our results suggest that mean EVI and NDVI successfully capture the effect of moisture variability on GPP at GRA and SSMF sites, including moderate drought conditions when GPP can actually increase because of increases in LAI (Nagy et al, 2007;Mirzaei et al, 2008;Aires et al, 2008).…”
Section: Interannual Variation In Gppsupporting
confidence: 59%
“…In GRA, correlations between anomalies in mean EVI (and NDVI) and anomalies in GPP suggest that interannual variability in GPP in grasslands is tightly coupled to leaf area and supports the hypothesis that grasslands use LAI regulation to avoid moisture stress (Jenerette et al, 2009). Our results suggest that mean EVI and NDVI successfully capture the effect of moisture variability on GPP at GRA and SSMF sites, including moderate drought conditions when GPP can actually increase because of increases in LAI (Nagy et al, 2007;Mirzaei et al, 2008;Aires et al, 2008).…”
Section: Interannual Variation In Gppsupporting
confidence: 59%
“…The degree of each is dependent on self-organizational processes and is in response to specific environmental variability (Carpenter et al, 2001). Often, there is a trade-off associated with the use of either strategy (Orwin et al, 2006;Jenerette et al, 2009). Often, there is a trade-off associated with the use of either strategy (Orwin et al, 2006;Jenerette et al, 2009).…”
Section: Resilience Resistance Stabilitymentioning
confidence: 99%
“…Models that emphasize the coupling between environmental and system variability will allow better descriptions of system functioning in response to the environment. Recently, theory and data for coupling detailed physiological models with whole-ecosystem measurements at half-hourly scales have shown great success (Desai et al, 2007;Jenerette et al, 2009;Medvigy et al, 2009). Jointly applying these and other statistical approaches to mechanistic models that resolve fine scale temporal resolution would facilitate linking systems theory with new high-resolution data sets (Ruddell and Kumar, 2009).…”
Section: Predictability and Modellingmentioning
confidence: 99%
“…Therefore, the main differences in the patterns of the CO 2 assimilation during the dry seasons between our two sites could be better explained by the differences between the vegetation types (species, green biomass amounts, canopy structures) as observed in Africa (Williams and Albertson 2005). Jenerette et al (2009) found over 3 years at San Pedro River in Southern Arizona, USA that the GPP values were consistently higher and less variable for the woodland than for grassland with some distinct rates and variability during the growing seasons. During the year, while the absolute ER/GPP ratio was relatively constant (71-80 %) for the forest, it was highly variable (69-157 %) for the savannah (Fig.…”
Section: Larger Ecosystem Respiration (Er) For the Forest Than Savannahmentioning
confidence: 88%